Hemicellulose extraction from slash pine sawdust by steam explosion with sulfuric acid - Stoffel, Romina Bettiana (2017)
One of the main obstacles to the development of advanced forest biorefineries is the optimal fractionation of the plant biomass. The aim of this work was to design a two-stage process for the fractionation of slash pine sawdust: alkaline deresination for extractives removal and sulfuric acid-catalyzed steam explosion (SE) for hemicellulose extraction. SE was carried out in a high-pressure steam reactor under different conditions of temperature (180 °C–200 °C), time (5 min–10 min) and acid concentration (1:100 H2SO4 - 3:100 H2SO4 (on mass of dry wood)) according to a factorial design. Extractives, lignin, carbohydrates, and degradation by-products were quantified. The effect of pretreatment on enzymatic hydrolysis (EH) was also evaluated. SE was very efficient for hemicelluloses extraction (90% at 200 °C with 3:100 H2SO4 (on mass of dry wood) for 5 min) with a high glucan recovery. EH yield increased 6-fold after SE. There was a trade-off between maximizing carbohydrate recovery, hemicellulose extraction, and cellulose digestibility.